Hydro-chemical study and assessment of drinking and irrigation water quality in the Oued Fez watershed (Fez city and surrounding areas, Saïs Basin, Morocco) - Ayman Agharabi; El Mehdi Jeddi; Lhoucine Karrat; Nicolae Har; Ahmed Ntarmouchant; Ferenc Lazar Forray; Lahcen Gourari; Constantin Balica; Cristian Victor Mircescu; Brahim Mali; Horea Bedelean (Environmental Advances)
The Saïs basin, which in its northeastern part includes the city of Fez, is located in northern Morocco, between Middle Atlas and Pre-Rif mountains. It is drained by a hydrological system that supports agricultural, urban and industrial activities in this semi-arid region. This system is weakened by anthropic impact, hence the importance of assessing the quality of these waters for better management and preservation.This study evaluates the physicochemical characteristics, hydrochemical evolution and suitability for drinking and irrigation of surface waters in the Oued Fez basin (OFB). The hydrochemistry reveals average cation and anion concentrations (mg/l) organized in decreasing order: HCO3- (140.8) > Cl- (110.4) > Na+ (85.6) > Ca2+ (31.7) > SO42- (23.8) > NO3- (23.5) > Mg2+ (16.7) > K+ (0.8). These concentrations vary from a Ca-HCO3 facies upstream to Na-HCO3 in the intermediate zone and Na-Cl downstream. These variations are controlled by water-rock interaction processes and by the significant influence of anthropogenic factor in areas with high urban density. Isotopic signatures vary between -7.09 and -5.68 ‰ for δ¹⁸O and between -42.7 and -32.8 ‰ for δ²H, confirming the meteoric origin of these recharged waters in the Middle Atlas between 1011 and 1577 m.The quality assessment of these waters for drinking purposes testifies to their acceptability, except for S-MC and R-FS4 located in urban areas. According to the quality indices for irrigation (SAR, Na %, PI, KI, IWQI), only downstream waters are unsuitable for this purpose, due to the high sodium and salinity risks associated with anthropogenic contamination.This work spatially shows the causes of changes in the chemical composition and suitability for irrigation of these waters. It identifies sources of pollution that can be avoided to preserve the health sustainability of these waters. It also highlights the influence of human activity and climate on this precious resource.